Taxonomia das vespas parasitoides do grupo de espécies vau de Conura Spinola (Hymenoptera, Chalcididae) - Santos Neto, José Pinheiro dos (2023)
Conura is the most species-rich genus in Chalcididae and is almost exclusively from the New World. It currently includes 306 described species and it is estimated that there are 770 species from Neotropical region. The species belonging to the genus are organized in 63 species group, among them are the neotropical vau species group, which assembles two described species, Conura (Conura) vau (Ashmead, 1904) e C. parides Tavares & Navarro-Tavares, 2006. Based in the analysis of specimens from several collections around the world, it was found some undescribed species, which corroborates the information recorded in literature. Therefore, This work presents a revision of vau species group, with redescription of the two previously described species and the description of eight new species. Additionally, an identification key and illustrations for all studied species are presented, further the description of new morphological characters for the group species. New data of geographic distribution for the species and for the species group are presented as well.